Migrant Workers’ Housing: A Case Study of the Wuling Mountain Area - Tian, Robert Guang; Xiao, Sidi (Advances in Social Sciences Research Journal, 2023)
Migrant workers’ urban housing meets their residential needs and represents their social rights and integration into the city. However, migrant workers live in poor housing conditions in cities with regional differences. The Wuling Mountain Area is located in the strategic intersection zone of the central and western regions. The area is highly attractive to migrant workers because of its economic and geographical location and low housing prices. It is a typical case to address migrant workers’ urban integration. In this paper, migrant workers’ urban housing was investigated in the Wuling Mountains area. It was found that their housing was in poor conditions, with inadequate housing facilities, an impoverished community environment, and insufficient supporting facilities. Given this, some policy recommendations were proposed. The government should make urban housing accessible to migrant workers and improve city housing conditions. In addition, migrant workers should be motivated to pay for urban housing and integrate into cities. Hence, it can provide practical implications for addressing migrant workers’ urban housing.